A brief history of telecommunication and transmitting information in Afghanistan (Journal of history, 2021)
During the ancient time the important way for communicate between people was face to face and direct communications. Therefore all activities of communicate were limited with small community and they could not be aware from state of other countries and their neighbors of the direct methods. In the review of communications and the evolution between people were some progress from the beginning and expand connections of themselves through their various inventions. People did not have much ability to talk, interact and communicate with each other. But with the developing of different sciences and their integration with each other the possibility of human interaction has increased in modern era, nowadays we see their unlimited communication with each other that we are in the era of new technol- ogy, we have witnessing for the extensive communication of people that beings with each other that they can easily communicate everywhere of the world. In the present time all communication tools such as internet, mobile phone, satellite, cinema, television, radio are available for using of modern people, which they can communicate with each other and can see each other faces from every zone of the world. All these developments originate from the rich thinking and intelligence of humanity. In Afghanistan dur- ing the 20th century after civil war the communication was also comfortable for using by supporting of subordinating countries via installing of modern technology.Key words: communication, satellite, data, post office, stamp, massages and television.